Composite heat sink LED cooling - Gibbons, Michael; Feng, C.; Chandra, S. (My University, 2018)
Metal coating of 3D printed polymers is an attractive proposition for thermal dissipation of light emitting diodes, due to its high efficiency and markedly lower material costs than conventional aluminum heat sinks. Efficient thermal cooling of light emitting diodes is essential in maintaining electronic and optical performance. The thermal performance of three heat sink designs were experimentally investigated for three applied heat fluxes (0.5-1.5 W cm-2). The results show that metal coating of the polymer heat sinks enables significant heat transfer enhancement of 37% over the uncoated case. The inclusion of an aluminum insert into the base of the composite heat sink design, in tandem with the zinc coating reduced on chip temperatures by 27% over the zinc coated case for the greatest applied heat flux.
The Canadian Society for Mechanical Engineering International Congress 2018
Keywords: Light emitting diode; Heat transfer; Metal spray coating; Composite heat sink; Composite heat sink; HEAT TRANSFER; LIGHT-EMITTING-DIODES; Metal spray coating